‘We Often Forget It Was a Disaster’: Cross-Curricular Teacher Collaboration to Develop a Curriculum Unit on the Titanic Disaster: ‘We Often Forget It Was a Disaster’: Cross-Curricular Teacher Collaboration to Develop a Curriculum Unit on the Titanic Disaster - Park, Wonyong; Shaby, Neta; Newman, Rachele (Science & education, 2025)
There is a growing emphasis on integrating school subjects and cross disciplinary boundaries to address local and global challenges, particularly when teaching about complex and sensitive issues such as disasters. This study explores how the integration of science and history can facilitate learning about disasters through a cross-curricular teacher professional development project in England. Seven teachers (four history, three science) from state-funded secondary schools and two museum educators in Southampton, UK collaborated with university researchers over eight months to develop a curriculum unit on the Titanic disaster for Key Stage 3 pupils (aged 11–14). Through a qualitative analysis of teacher feedback, workshop recordings and artefacts, and interviews, we illustrate the teachers’ initial excitement at the prospect of cross-curricular integration and how this excitement was then tempered by practical and logistical challenges that prevented their integration ideas from materialising into the curriculum unit. Nevertheless, teachers found that the CPD helped them to see and attend to the connections across the curriculum. Teachers rediscovered Titanic as a tragic event with historical significance for local students, which needs to be taught with reverence and ethical sensitivity. Using the Titanic disaster as an example, the study points to the potential for cross-curricular integration and teacher collaboration in teaching about disasters holistically in secondary schools.